Balancing acts : studies in counselling training - Johns, Hazel (Routledge, 1998)
"In this book, counsellors, trainers and supervisors discuss the tensions, conflicts and complexities involved in many of the aspects of being a trainer, being a trainee and the elements of counselling training itself. Through innovative research and lively first-hand accounts, Balancing Acts explores both individual trainer development and course design and management in counselling and other training contexts in the helping professions." "Using both research and the reflections of experienced counsellors to explore issues that affect their professional practice, Balancing Acts is a valuable resource for all those involved in adult learning."--Jacket